PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN PERMAINAN MONOPOLI - Yulia Dwi P (Pendidikan Ekonomi, 2010)
The study was intended to find out the activities of the teacher and students, the learning results and responses of the students after the monopoly game was used in the instruction on Badan Usaha. The study was classroom action research, consisting of three cycles. The subjects were 30 seventh graders of class B at MTs Al-Muttaqin Plemahan, Kediri. The data were analyzed by using quantitative and descriptive analyses. The results showed that the activities of the students and teachers the learning and teaching process by using monopoly game increased. It also found that the learning results of the lesson of the students also increased. The students also showed positive response to the use of monopoly game in the instructional process.